Sex- and trait-specific contribution of individual- and population-level processes to age-related changes in multiple plumage ornaments - Enrique González-Bernardo; Jesús Martínez-Padilla; Carlos Camacho; Marta E. García del Castillo; Jaime Potti; David Canal (iScience)
Summary: Individuals experience changes in multiple traits across their lifespan, often peaking before senescence-driven declines. Many species display secondary sexual traits that can vary with age due to physiological and selective processes, influencing individual fitness and sexual selection. Using 13 years of longitudinal data from a pied flycatcher (Ficedula hypoleuca) population, we analyzed age-related variation in wing and forehead patches in both sexes. Wing patch size increased with age due to both within- and between-individual effects, with sex-specific patterns. Forehead patch size showed sex-dependent age effects: quadratic in females, linear in males, with only males exhibiting within-individual changes. In females, forehead patch occurrence followed a quadratic age pattern, influenced by selective (dis)appearance and reproductive timing. These results show that age-related ornament expression arises from different processes across traits and sexes, highlighting potential trade-offs between reproduction and ornamentation. This study underscores the role of both sexes’ ornaments in selection and life-history strategies.